The effect of views through windows on apartment dwellers in an urban setting: a case study of hyderabad apartment - Tanveer, Sara; Qureshi, Sabeen; Rasool, Asifa (Penerbit Universiti Kebangsaan Malaysia, 2023)
The rate of urbanisation is increasing in Pakistan as it develops. The connection to nature, however, is receding in urban settings as the country grows. Apartment buildings have been recognized as a characteristic type of urban housing due to the increasing intensity of land use in urban areas. In Hyderabad, one of the neglected aspects of urban living is the neglect of window design, orientation, and view through the window in apartment buildings. Windows are the primary means of communication between the inside and outside of the building. This paper highlights the significance of window views in urban setting in relation to sustainable development. Furthermore, the purpose of this research is to investigate the effect of window views on apartment dwellers in Hyderabad and how it affects the sustainability of a building. The case studies were conducted on apartments in Qasimabad, along with a questionnaire survey based on the residents' preferences for window views and how the existing setting affects their behavior. After analyzing literature, conducting case studies, and completing a survey questionnaire, results suggest that window views promote pleasant emotions, productivity, health, and well-being, which contribute to a sustainable development